On Frictional Forces between the Finger and a Textured Surface during Active Touch - Janko, Marco; Primerano, Richard; Visell, Yon (IEEE transactions on haptics, 2016)
We investigated forces felt by a bare finger in sliding contact with a textured surface, and how they depend on properties of the surface and contact interaction. Prior research has shed light on haptic texture perception. Nevertheless, how texture-produced forces depend on the properties of a touched object or the way that it is touched is less clear. To address this, we designed an apparatus to accurately measure contact forces between a sliding finger and a textured surface. We fabricated textured surfaces, and measured spatial variations in forces produced as subjects explored the surfaces with a bare finger. We analyzed variations in these force signals, and their dependence on object geometry and contact parameters. We observed a number of phenomena, including transient stick-slip behavior, nonlinearities, phase variations, and large force fluctuations, in the form of aperiodic signal components that proved difficult to model for fine surfaces. Moreover, metrics such as total harmonic distortion and normalized variance decreased as the spatial scale of the stimuli increased. The results of this study suggest that surface geometry and contact parameters are insufficient to account for force production during such interactions. Moreover, the results shed light on perceptual challenges solved by the haptic system during active touch sensing of surface texture.